The impact of vaccination strategies for COVID-19 in the context of emerging variants and increasing social mixing in Bogotá, Colombia: a mathematical modelling study (2021)
In Bogotá by August 1st, more than 27,000 COVID-19 deaths have been reported, 29 while complete and partial vaccination coverage reached 30% and 37%, respectively. Although 30 reported cases are decreasing, the potential impact of new variants is uncertain.